2023
DOI: 10.3389/fpubh.2022.1087138
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed access to COVID-19 vaccines in low- and lower-middle-income countries

Abstract: IntroductionA majority of low-income (LIC) and lower-middle-income countries (LMIC) were unable to achieve at least 10% population coverage during initial vaccine rollouts, despite the rapid development of the coronavirus disease 2019 (COVID-19) vaccines. Nearly three years into this pandemic, evaluating the impact of inequities in vaccine access, uptake, and availability is long overdue. We hypothesized that a delay in receiving COVID-19 vaccines was associated with an increased toll on cumulative cases and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…27 Low vaccination rates in low-and-middle-income (LMICs) African countries are partly due to the inequitable distribution of vaccines caused by constrained financial resources to support competing priorities in underdeveloped health systems and bottlenecks in the supply chain which may lead to delayed vaccine rollout. 28,29 Studies have also reported that pregnant women did not receive COVID-19 vaccines due to their limited availability in Africa, perhaps an indication of the inability of pharmaceutical companies to manufacture vaccines in Africa, and the compromised quality of the vaccines manufactured by international pharmaceutical companies for the African market. 27,30 COVID-19 vaccination uptake is also hampered by the low-risk perception of the pandemic, concern about adverse vaccine effects, low vaccination awareness, and low acceptance, intention and willingness to get vaccinated.…”
Section: Vaccine Uptake Over Timementioning
confidence: 99%
“…27 Low vaccination rates in low-and-middle-income (LMICs) African countries are partly due to the inequitable distribution of vaccines caused by constrained financial resources to support competing priorities in underdeveloped health systems and bottlenecks in the supply chain which may lead to delayed vaccine rollout. 28,29 Studies have also reported that pregnant women did not receive COVID-19 vaccines due to their limited availability in Africa, perhaps an indication of the inability of pharmaceutical companies to manufacture vaccines in Africa, and the compromised quality of the vaccines manufactured by international pharmaceutical companies for the African market. 27,30 COVID-19 vaccination uptake is also hampered by the low-risk perception of the pandemic, concern about adverse vaccine effects, low vaccination awareness, and low acceptance, intention and willingness to get vaccinated.…”
Section: Vaccine Uptake Over Timementioning
confidence: 99%
“…The Africa region represents one-fifth of the global population, but in 2021 it received just 3% of all COVID-19 doses 16. While the number and types of vaccines delivered to the Global South have increased over time, countries in the Global South have been the most disadvantaged in obtaining access to the most effective vaccines 17. Prices for some vaccines were sometimes higher in the Global South than in the Global North (see table 1).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic study to assess the impact of delayed supply of COVID-19 vaccines indicated that only 25% of the population in low-and lower-middle-income countries received at least one dose of vaccine as of October 2022. 1 Ensuring an adequate supply of COVID-19 vaccines for low-and lower-middle-income countries (LMICS), which constitute 85% of the global population, is essential. The rapid rollout of COVID-19 vaccines saved millions of lives globally.…”
Section: Introductionmentioning
confidence: 99%